A case of retroperitoneal dedifferentiated liposarcoma successfully treated by neoadjuvant chemotherapy and subsequent surgery - Yukihiro Yokoyama; Yoshihiro Nishida; Kunihiro Ikuta; Masato Nagino (Surgical Case Reports, 2020)
Abstract Background Retroperitoneal liposarcoma (RPLS) is the most commonly observed soft tissue sarcoma in the retroperitoneal space. Although the beneficial effect of chemotherapy for RPLS is controversial, there are some reports that have shown a considerable tumor-suppressive effect of chemotherapy in RPLS. We demonstrate a case of dedifferentiated RPLS, which was initially considered inoperable but was successfully treated by neoadjuvant chemotherapy and subsequent curative resection. Case presentation A 59-year-old female was referred to our hospital with a chief complaint of right lower quadrant abdominal pain. Abdominal computed tomography revealed a large retroperitoneal tumor with a maximum diameter of 11 cm. The tumor involved retroperitoneal major vasculatures, such as the right common iliac vein and artery, as well as the right psoas muscle and femoral nerve. The right ureter was also involved and obstructed by the tumor. A biopsy was performed through the retroperitoneal route, and the tumor was diagnosed as a dedifferentiated liposarcoma with the Fédération Nationale des Centres de Lutte Contre le Cancer grade 3. Because the tumor was highly invasive and complete resection was not feasible, we decided to administer neoadjuvant chemotherapy with doxorubicin and ifosfamide (AI). After completing 6 courses of AI, the tumor size was considerably reduced, and we decided to perform surgery with curative intent. Before laparotomy, femoro-femoral arterial bypass was performed to prepare for the right common iliac artery resection. Thereafter, the patient underwent laparotomy and tumor resection combined with right nephrectomy, resection of the right common iliac artery and vein, and resection of the right psoas muscle and femoral nerve. The postoperative course was uneventful, although the patient needed a walking brace to support her gait. The pathological findings indicated a 99% disappearance of tumor cells. The patient was healthy without any complaints after 1 year of surgery, and a follow-up CT scan revealed no tumor recurrence. Conclusions To the best of our knowledge, this is the first report that showed a nearly complete pathological response to AI in dedifferentiated RPLS, which was subsequently completely resected.